Hubungan Partisipasi Penyusunan Standar, Keketatan Standar dan Insentif Berbasis Standar dengan Kinerja (Pengujian Hubungan Langsung dan Tidak Langsung) - Etty Murwaningsari (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2009)
This research aims to investigate the relationship between participative standard setting, standard tightness and standard-based incentives toward public accountant performance and work-related stress. The research examined 16 Jakarta-based public accounting firms in 2007 involving 213 respondents––112 from big-four public accounting firms and 101 from non-big-four public accounting firms. The statistical method used to test the hypothesis is the Structural Equation Model (SEM). Empirical results from observing a big-four public accounting firm using a direct model examining five variables show that four variables have significant correlation, while an indirect model examining six variables results in two variables have significant correlation. Moreover, an observation of a non-big-four public accounting firm using a direct model examining five variables show that four variables have significant correlation, while examination of six variables using an indirect model found that five variables have significant correlation.